STRATEGI PENINGKATAN KUALITAS GURU TAHSIN AL-QUR'AN DI RUMAH TAHFIDZ SAFINATUL JINAN KABUPATEN BOGOR - Akhmad Riqordi; Kaimudin; Zaenal Abidin; Edy (Dakwatussifa: Journal of Da'wah and Communication, 2026)
Abstract: This study investigates the crucial role of enhancing the quality of Tahsin teachers at Rumah Tahfidz Safinatul Jinan, aiming to foster an effective and high-caliber Quranic learning ecosystem. The research underscores that the proficiency of Tahsin teachers, encompassing their mastery of Makharijul Huruf, Tajwid principles, fluency in recitation, and adherence to Quranic etiquette, is paramount in developing students' ability to read the Quran accurately and beautifully. Empirical findings reveal a significant positive correlation between interventions aimed at improving teacher quality and increased student scores in Tajwid comprehension and practice, aligning with constructivist learning theories that emphasize the educator's role as a facilitator. The study highlights that qualitative improvements in teachers, including their depth of Tajwid knowledge and pedagogical skills, are indispensable for creating meaningful learning experiences. Furthermore, expert opinions emphasize that teacher quality is the bedrock for the future generation's Quranic proficiency. Evidence indicates that investments in Tahsin teacher development have led to a substantial reduction in student recitation errors, particularly in complex areas like Madd and Ghunnah. Effective teacher training empowers educators to identify and address the root causes of student errors, moving beyond mere correction to foster genuine understanding. Ultimately, enhancing teacher quality is identified not merely as a training program but as a strategic long-term investment with broad implications for cultivating strong Quranic character and fostering a deep connection with the Holy Book. This endeavor is supported by the integration of academic competence with moral and spiritual development, the establishment of robust evaluation and supervision systems, the cultivation of a progressive learning culture, strategic utilization of digital technology, and the provision of adequate welfare and recognition, all of which are vital for producing holistic, Quran-oriented individuals and maintaining the institution's repute. Keywords: Tahsin Teachers, Quranic Education, Teacher Quality Improvement, Tajwid, Rumah Tahfidz Safinatul Jinan